2022. Evaluation of Antimicrobial Prophylaxis and Infectious Outcomes in Penile Prosthetic Implants at VA Long Beach Healthcare System. (15th December 2022) - To, Anna; Tran, Thuong; Tan, Susanna; Chun, Patricia
Abstract: Background: Penile prosthetic implants (PPI) offer an effective treatment for erectile dysfunction. The risk of postoperative infection in primary PPI is estimated at 0.33-11.4% and up to 18% in revision surgery. The most common causative organisms include Escherichia coli and coagulase negative Staphylococcus. The AUA guidelines recommend perioperative antibiotics for no more than 24 hours. However, a survey of urologists revealed that the majority used oral antibiotics for 5-14 days after surgery. There have been increasing reports of anaerobic and fungal infections, but the AUA guidelines do not recommend antimicrobial prophylaxis against these organisms. Methods: This is a retrospective, chart review, quality-improvement study. Veterans who had a PPI procedure between May 1999 to July 2021 were included. Patients with only removal of the prosthesis were excluded. For patients who had multiple procedures, only the most recent procedure was considered. Data collection included demographics, pertinent medical history (history of polysubstance abuse, homelessness, smoking, chronic immunosuppression, anticoagulation, diabetes, HIV, spinal cord injury, Peyronie's disease or priapism), prior PPI, relevant labs (BMP, A1C), microbiologic results, and medications prescribed. Results: 176 patients underwent a PPI-related procedure between May 1999 and July 2021. 137 patients were included in this study. 14 patients (10.2%) experienced a PPI infection. For all patients, the average total duration of antimicrobial prophylaxis was 11.8 days. Mean duration of antimicrobial therapy after procedure was 12.4 days and 10.5 days for the infection and no infection group, respectively (p-value 0.118). The most common antibiotic combination was vancomycin and gentamicin. There were no statistically significant difference in patient risk factors between infection and no infection groups, but the most common risk factors were smoking and prior implant. Gram positive organisms were most commonly isolated. There were no incidences of fungal infections. 2.2% incidence of AKI and 1.5% incidence of antimicrobial resistance were observed. Conclusion: Further evaluation of the necessity of prolonged duration of antimicrobial prophylaxis and antifungal prophylaxis should be evaluated. Disclosures: All Authors : No reported disclosures.